2016
DOI: 10.1007/s12035-016-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Hippocampal Oligodendrocytes Contributes to the Deficit of Contextual Fear Learning in Adult Rats Experiencing Early Bisphenol A Exposure

Abstract: During early development, continuous exposure to environmental contaminants such as bisphenol A (BPA) is known to alter neuronal development, resulting in aberrant brain structure and predisposing individuals to developing neuropsychiatric disorders later in life. While the altered oligodendrocyte (OL) structure and function have been casually linked to the occurrence of numerous psychiatric diseases, it remains open whether early BPA exposure (EBE) also recruits OLs to mediate its toxicity in the brain. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Following a full text review, a list of potential test chemicals was generated, containing nine substances (Figure S1). This list included cuprizone [70], toluene [71], bisphenol A (BPA) [72,73], BDE-99 [74,75], ethanol [76][77][78][79], methyl mercury [80], Tris(1,3-dichloro-2propyl) phosphate (TDCPP) [81], vanadium [82][83][84], and lead [85,86] (Figure 1G). For this study, only four chemicals were selected from this list.…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…Following a full text review, a list of potential test chemicals was generated, containing nine substances (Figure S1). This list included cuprizone [70], toluene [71], bisphenol A (BPA) [72,73], BDE-99 [74,75], ethanol [76][77][78][79], methyl mercury [80], Tris(1,3-dichloro-2propyl) phosphate (TDCPP) [81], vanadium [82][83][84], and lead [85,86] (Figure 1G). For this study, only four chemicals were selected from this list.…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…Current evidence showed that both astrocyte–neuron and oligodendrocyte—axon lactate shuttles are important for the brain energy metabolism and support neuronal function and survival (Cater, Chandratheva, Benham, Morrison, & Sundstrom, ; Fünfschilling et al, ). Our previous work has found that early BPA exposure induced decreased expression of monocarboxylate transporter 1 (MCT1), a critical protein for transporting lactate from oligodendrocytes to myelinated axons, and more demyelinated axons in the adult hippocampus of BPA–treated rats (Xu et al, ). The decrease in lactate production (present study) and decreased MCT1 expression (previous study) in the adult hippocampus of BPA–exposed rats are likely to cause weakness of axonal energy metabolism and consequent demyelination of axons, which may be responsible for deficit of contextual fear learning in adult BPA–treated rats (Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…BPA is completely and rapidly absorbed from the gastrointestinal tract (Volkel, Colnot, Csanady, Filser, & Dekant, 2002). Our previous study has demonstrated that perinatal constant BPA exposure at a low dose of 0.1 mg/L via maternal drinking water, which is equivalent to about 15 μg kg -1 day -1 BPA intake (Xu et al, 2012), induced a mean BPA level of 1.7 ng/ml in serum in 21day-old pup rats which is lower than the mean value observed in girls and boys (Chen et al, 2015;Komarowska et al, 2015), and caused hyperactivity, impaired spatial memory and deficit of contextual fear learning in adulthood (Xu et al, 2014(Xu et al, , 2017. These evidences suggest that the serum BPA level in children is sufficient to lead to a spectrum of adverse consequences on brain development and behavior in rodents ranging from the hypotrophy of dendritic spine in the developing neurons to neuropsychiatric deficits (Xu et al, 2007(Xu et al, , 2013(Xu et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The idea that myelination is critical for normal cognitive function is also supported by rodent preclinical models that preferentially induce oligodendrocyte loss and demyelination of the corpus callosum (Xu et al, 2010 ), hippocampus (Xu et al, 2017 ) or medial prefrontal cortex (Yang et al, 2017 ) and impair working memory. Social isolation during development, which has no effect on oligodendrocyte number, but results in thinner myelin in the prefrontal cortex and hippocampus, also impairs working memory (Makinodan et al, 2012 ; Cao et al, 2017 ).…”
Section: Oligodendrocyte Lineage Cells Affect Learning and Cognitionmentioning
confidence: 99%